Examining the contribution of student anxiety and opposition-defiance to the internal dynamics of affective, Cognitive and Behavioural Engagement in Math. (June 2022) - Archambault, Isabelle; Pascal, Sophie; Olivier, Elizabeth; Dupéré, Véronique; Janosz, Michel; Parent, Sophie; Pagani, Linda S.
Abstract: Anxiety and opposition-defiance in children are negatively linked to their classroom performance. However, little is known about the additive contribution of these difficulties on student engagement in math, especially in children living in low-income neighbourhoods. Using a sample of 460 students from grades 3 to 5, this study examines whether the link between student anxiety and opposition-defiance at the beginning of the school year and their affective, cognitive, and behavioural engagement in math by the end of the subsequent school year is mediated by shorterterm level of engagement. Results of the path analyses suggest that anxiety and opposition-defiance can predict a hierarchically structured downward spiral in student engagement. Such result is worrisome, given that fostering and honing good social, emotional, and cognitive academic skills in children forecast personal and economic success during the life course. Implications for theory and practice are discussed. Highlights: Anxiety/opposition-defiance present short-term risks on student disengagement. A structured mediation process links anxiety, opposition-defiance and disengagement. Anxiety/opposition lead to a downward spiral from emotions to thoughts to actions.